2020
DOI: 10.1021/acs.jpcc.0c01698
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Chemical Stability of Li1.4Al0.4Ti1.6(PO4)3 Solid Electrolyte with Various Cathode Materials for Solid-State Batteries

Abstract: In a solid-state battery (SSB) system, undesirable electrode−electrolyte interfacial reactions lead to a significant performance degradation. Herein, we performed a systematic study on the chemical stabilities between Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 (LATP) solid electrolyte and various cathode materials at their adhesion temperatures of 500−900 °C. Quantitative analysis of X-ray diffraction (XRD) data using Rietveld refinement revealed that Li-concentration disparity between LATP and oxide cathode materials (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…Yu et al 119 revealed more details of the interfacial thermal reactions between LATP and three different‐structured cathodes (layered, spinel, and olivine) through Rietveld refinement of XRD. Layered‐structured cathodes initially decompose into transition‐metal oxides, from which lithium ions diffuse into LATP at the same time.…”
Section: Interface‐level Thermal Stability Of Sesmentioning
confidence: 99%
“…Yu et al 119 revealed more details of the interfacial thermal reactions between LATP and three different‐structured cathodes (layered, spinel, and olivine) through Rietveld refinement of XRD. Layered‐structured cathodes initially decompose into transition‐metal oxides, from which lithium ions diffuse into LATP at the same time.…”
Section: Interface‐level Thermal Stability Of Sesmentioning
confidence: 99%
“…[41] Also, there have been studies using LATP as a surface coating layer for various cathodes to enhance structure stability and to resist electrolyte erosion, and great electrochemical stability has been found even at a high cycling temperature of 150 C. [89,90] However, due to the rigid nature of oxide electrolytes, the LATP/cathode interface still suffers from poor contact. Yu et al studied the high-temperature (500-800 C) chemical stability between LATP and various cathode materials and found that although a thermodynamically stable phase formed at the LATP/LFP interface at a temperature lower than 500 C, the interface between LATP and a layered or spinel cathode can degrade at 600-700 C due to disparity of Li concentrations, [91] which is consistent with the report by Gellert et al that oxide cathodes are highly reactive to LATP at a sintering temperature as low as 500 C. [92] Therefore, research on low-cost, effective LATP/cathode interfacial engineering is still needed.…”
Section: Latp Solid Electrolytementioning
confidence: 99%
“…XPS provided evidence of a limited interfacial reaction between LMO and LLZO [113] . LiFePO 4 reacts severely with LATP at low temperature (T<500 °C) and produces NASICON Li 3 M 2 (PO 4 ) 3 (M=Fe and others) [114] …”
Section: Stabilities and Interfaces Of Inorganic Ssesmentioning
confidence: 99%
“…[113] LiFePO 4 reacts severely with LATP at low temperature (T < 500°C) and produces NASICON Li 3 M 2 (PO 4 ) 3 (M=Fe and others). [114] In summary, there are two main sources of interface resistance between the oxide-based SSEs and the cathode materials. One is the reaction between the electrolyte and the cathode material to generate an interface phase.…”
Section: Sses/cathode Interfacesmentioning
confidence: 99%